ENGLISH EDUCATION STUDENTS CLASSROOM MANAGEMENT PROBLEMS DURING THE SCHOOL PRACTICE PROGRAM - Bonaventura Estu Parasdya (Sanata Dharma University, Yogyakarta, 2020)
This research aims to answer two research problems, namely: What are the English Language Education Study Program (ELESP) practice teaching students classroom management problems during the School Practice Program? Second, what are the solutions to the ELESP practice teaching students classroom management problems during the School Practice Program? To answer the research problems above, the researcher used a quantitative method in the form of descriptive research. The instruments were a questionnaire and an interview. Based on the data gathered, most of the practice teaching students gave positive responses on the close-ended statements distributed to the students of the English Language Education Study Program of Sanata Dharma University, Yogyakarta. From the four classifications of classroom management components, the researcher found that management of discipline was the only classification received negative responses. Besides, the open-ended question generated other problems. As a result, a total of eight problems were found based on the questionnaire analysis and were categorized into teacher factors, student factors, and school factors. Furthermore, the major solutions to the problems were setting rules, designing interesting learning activities, approaching directly, and giving caution and rewards. Finally, the researcher also gave recommendations to ELESP lecturers, future practice teaching students, and future researchers.